Self esteem Peserta Didik dalam Implementasi Pendidikan Inklusi - Ida Zuraidah; Lalu Hamdian Affandi; Ilham Syahrul Jiwandono (Pendagogia: Jurnal Pendidikan Dasar, 2021)
The diversity of learners in the School of Inclusion becomes a challenge in the education’s world. Where, special needs learners will find themselves unlike the majority of people around them. This affects the individual's self-view which has an impact on self esteem, thus disturbing psychological well-being. For this reason, this study aims to find out in depth how self esteem of learners and the acceptance of people around students with special needs in the School. This research uses qualitative approaches with descriptive methods through field studies that examine various aspects through primary data sources, namely observations and interviews. Meanwhile, secondary data sources are obtained through documentation. The data obtained is analyzed through collection, condensation, presentation, and conclusions according to Miles, Huberman, and Saldana until the data obtained is credible. For the validity of this research data uses source and techniques triangulations. This research is expected to be an enhancer of the insights of every party involved in the implementation of inclusion education in order to respond as appropriate, so that self esteem develops well. The results of the study with students of class V SD Negeri 20 Mataram as a research setting showed self esteem of learners in the implementation of higher inclusion education. In addition, special needs learners are well received by those around them when they are in school.